2010
DOI: 10.3928/01913913-20100308-07
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Rectus Muscle Transposition for Correcting Abduction Deficiency in Duane's Syndrome Type 1 and Sixth Nerve Palsy

Abstract: The Scott Foster procedure is effective for improving deviation, abduction deficiency, and face turn in patients with Duane's syndrome type 1 and especially in those with sixth nerve palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 20 publications
0
12
0
4
Order By: Relevance
“…These findings were consistent with reported rates in the literature. [4][5][6][7][8] However, 96% of patients had fissure-narrowing/globe retraction on adduction, which was higher than reported rates in the literature. [9][10][11][12][13] The majority of our patients were classified as Duane group I (56%) followed by group III (28%) and group II (16%).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…These findings were consistent with reported rates in the literature. [4][5][6][7][8] However, 96% of patients had fissure-narrowing/globe retraction on adduction, which was higher than reported rates in the literature. [9][10][11][12][13] The majority of our patients were classified as Duane group I (56%) followed by group III (28%) and group II (16%).…”
Section: Discussionmentioning
confidence: 66%
“…[4][5][6][7][8]14,15 In our surgical subset of 18 patients (14 type I and 4 type II), the majority had an excellent surgical outcome with significant improvements in AHP and FPP alignment.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…3 In Yazdian et al, only 3 of 62 patients had induced vertical deviations. 22 But other studies have reported a larger percentage, with larger deviations ranging from 8.5% with deviations larger than 8Δ in Ruth et al on patients with Duane syndrome, to 20%–40% in abducens palsy. 8,18,23,24 As in our patient who developed a recurrent vertical deviation, Phamonvaechavan et al reported on the number of patients with vertical deviations increasing at the 6–10 week postoperative visit.…”
Section: Discussionmentioning
confidence: 87%
“…Rosenbaum [6] reported improvement in abduction from −3.9 to −2.8 after augmented transposition of the vertical rectus muscles in 42 patients with unilateral DRS, and-3.7 to −2.6 after non-augmented transposition of the vertical rectus muscles in 22 patients with unilateral DRS. Yazdian et al [7] improved abduction limitation from −4.00 ± 0.23 to −2.11 ± 0.48 after augmented transposition of the vertical rectus muscles in 38 patients with type 1 DRS. Britt et al [8] reported −2.5 to −4.0 abduction limitation after partial vertical rectus muscle transposition with augmented suture in 5 patients with DRS.…”
Section: Discussionmentioning
confidence: 99%